TINGKAT PENGETAHUAN TB PARU MEMPENGARUHI PENGGUNAAN MASKER PADA PENDERITA TB PARU - Yuliastuti, Christina; Novita, Nur Wachida; Narsih, Siti (Universitas Nahdlatul Ulama Surabaya, 2014)
Number of patients with pulmonary TB increased annually in Surabaya, on of the measures to prevent TB infections is by using a mask. In TB care room a lot of visitors (family) who did not wear a mask. The purpose of this study to determine the relationship between the knowledge level of Tuberculose with the masks using among visitors (family). This study used correlational analytic design with cross sectional approach. independent variable in the study is the level of knowledge about Tuberculose and dependent variable is the using of masks. Samples were taken by using simple random sampling technique earned by 28 respondents. Data collection was undertaken using questionnaire about Pulmonary Tuberculose and observation sheet of the using of mask. Data were analyzed with Spearman's Rho test with a significance level Corellation ? <0.05. Results showed that the level of knowledge about Tuberculose less 14 respondents (50%) and 16 respondents (57.1%) did not wear a mask. Spearman's Rho test showed that there is a relationship between the level of knowledge about Pulmonary Tuberculose with the using of masks in Pulmonary Wards,  Dr. Ramelan Navy Hospital, Surabaya (? = 0.000). The implications of this study is the level of knowledge about Tuberculosis associated with using of a mask, which is expected for nurses in the room can provide health education about and prevention of pulmonary Tuberculose transmission by using a mask.